Participación de los padres de familia en el proceso de enseñanza- aprendizaje - Chanatasig Toapanta, Norma Dolores (2017)
Participation processes are considered as heterogeneity context where people actions are not determined by external forces or conditions but are the result of a complex network of suggestions, declines, oppositions, internal and external discussions cause of educational perceptions from the people involved. Specially parents, teachers, and the whole school, in this way parents are the activate subjects which set common aims and share cultural backgrounds which identify and give an organization in education. Participation concept is used with the purpose of open a wide range of possibilities according to the changes and ways that school, educational politics and parents have taken. For this reason, this project is focused on parents’ participation in education. Keeping in mind parents’ participation involves giving advice how to build, produce and transform social life, that is why this project tries to get close parents in education. Family is the first school that children have and realize the main role that it takes in education. Nowadays there is not communication among teachers and parents, it has repercussions in children development. it leads school and family problems as; unmotivated, demotivation, dependence, low performance, failing, bulling, etc., The society, family, mates, do not have the fault of this, but the interaction of all of them trigger this.